Endojen okronozis: Bir alkaptonüri olgusu - (:unkn) unknown (My University, 2002)
Alkaptonüri, nadir görülen otozomal resesif geçişli bir doğumsal metabolizma hastalığıdır. Tirozin ve fenilalanin katabolizmasında rol alan "homogentisik asit oksidaz" enzimi eksikliği sonucu özellikle bağ dokusunda "homogentisik asit" (HGA) 'in birikmesi ile karakterizedir. Burada nadir görülen, bebeklik ve çocukluk dönemi bulguları olmaksızın erişkin dönem bulguları ile kendini gösteren bir alkaptonüri olgusu sunulmaktadır.

Alkaptonuria is a rare autosomal recessive disorder of inborn errors of metabolism. It is characterised by "homogentisic acid" (HGA) deposition especially in the connective tissue as a result of deficient "homogentisic acid oxidase" enzyme which has a role in the catabolism of tyrosine and phenylalanine. Here is presented, a rare alkaptonuria case, manifested with adulthood signs, in whom the infantile and childhood signs were not observed.
Endogenous ochronosis: An alkoptonuria case
Keywords: Dermatoloji; Pediatri